Psychological Well-Being Narapidana Remaja - Rahmi, Akmil; Pratiwi, Chici; Wijaya, Agung Satria (Institut Agama Islam Sumatera Barat Pariaman, 2021)
Adolescent prisoners experience difficulties in conforming, loosing freedom, feeling lonely, and adapting to the environment at the first time living in the correctional institution affecting psychological well-being condition. This study aims to observe the description of adolescents Prisoners’ psychological well-being. This study uses quantitative approach that is analytical descriptive method. The instrument used in this study is questionnaire that has 0.731 reliability (Cronbach’s Alpha). The subjects of this study were all adolescent prisoners in LPKA class II, Tanjung Pati which are in total 23 prisoners. This study’s result shows that psychological well-being of adolescent prisoners are in the high category, the details are that 1 prisoner in excessive category (4.35 %), 20 prisoners in high category (86,96 %), and 2 prisoners in moderate category (8.7%). Keyword: Psychological Well-Being, Young Prisoners, Guidance and Counseling